Optimasi Distribusi Biaya Transportasi Melalui Metode Modified Distribution - Marzuki, Ahmed Syarief; Juhari, Juhari; Alisah, Evawati (Jurnal Riset Mahasiswa Matematika, 2022)
Distribution is the action or process of supplying goods to stores and other businesses that sell to consumers. If a product or service is distributed from a company, it requires adequate means of transportation and usually requires too large distribution costs. Delivery of goods at this company does not use mathematical methods in calculating its distribution to several places correctly. The purpose of this research is to create an optimal, efficient and effective distribution model for this company by applying the North West Corner Method and the Modified Distribution Method in July, August and September 2021. North West Corner Method for the initial solution and Modified Distribution Method as the optimal solution is a variation of the Stepping Stone method. The results of this research show that the distribution costs incurred by the company after being calculated using the North West Corner Method and the Modified Distribution Method are Rp. 6,961,779, - from Rp. 7,000,000. Then these two methods are able to help companies save distribution costs incurred.